THE ROLE OF INTERPERSONAL COMMUNICATION IN BUILDING LEADERSHIP THAT POSITIVELY IMPACTS BUSINESS PERFORMANCE IN THE ENTREPRENEURIAL CONTEXT - Kusbandono, Danu; Az Zaakiyyah, Hizbul Khootimah; Junaidi, Ahmad (Technopreneurship and Educational Development Review (TENDER), 2024)
Leadership is a key determinant of business success or failure, particularly in the context of entrepreneurship. Effective leaders can steer vision, inspire teams, and navigate challenges faced by new ventures. This research explores the role of interpersonal communication in cultivating leadership that positively impacts business performance, specifically within entrepreneurial contexts. The research methodology employed is a literature review using qualitative approaches and descriptive analysis. Google Scholar serves as the primary source for data retrieval spanning from 2017 to 2024. Findings indicate that interpersonal communication plays a crucial role in shaping effective leadership in dynamic and evolving entrepreneurial contexts. By fostering strong relationships, inspiring corporate vision, facilitating effective coordination, and managing conflicts wisely, interpersonal communication serves not only as a tool for transmitting information but also as a foundation supporting long-term business success and growth.